Cutting Migration and Core Disturbance Caused by the Hydraulic Structure of Pressure- and Gas-Maintaining Coring Bits. (4th May 2022) - You, Zhenxi; Chen, Ling; Li, Cong; Liu, Guikang; Ye, Banghua; Shi, Xiaojun
Abstract : Gas disaster prevention and control is essential to coal mine safety production, with accurate measurement of gas pressure and content being the challenging key aspect. Pressure- and gas-maintaining coring devices can characterize cores in situ to achieve this accurate measurement. As an important part of these devices, the hydraulic structure of the coring bit plays a decisive role in the migration, coring rate, and core disturbance of the bottom-hole cuttings, and studying this structure is thus of great significance. In this paper, the fluid simulation software FLUENT is used to carry out numerical simulation of the bottom-hole flow field to study the cutting movement and core disturbance caused by coring bits with different hydraulic structures. The results show that (1) the best nozzle azimuth angle of 75° is beneficial to bottom-hole cutting discharge and reduces the scouring effect of the drilling fluid on the core. (2) The larger the diameter of the nozzle of the coring bit is, the weaker the cutting removal ability of the drill bit and the smaller the cutting scouring effect of the drilling fluid. The optimal nozzle diameter is 12 mm. (3) Adding a sluice channel inside the water barrier ring can reduce the erosion of drilling fluid on the core. (4) Bits with a rectangular inner passage promote cutting migration. Field application results show that the designed coring bit performs well, and the research results can provide a reference for the structure optimization of coring bits for pressure and gas retention.